New (α β γ)-incommensurate magnetic phase discovered in the MnCr2 O4 spinel at low temperatures - Pardo Sainz, M.; Toshima, A.; André, G.; Basbus, Juan Felipe; Cuello, G. J.; Laliena, V.; Honda, T.; Otomo, T.; Inoue, K.; Hosokoshi, Y.; Kousaka, Y.; Campo, J. (American Physical Society, 2023)
Fil: Pardo Sainz, M.. Universidad de Zaragoza; España